(untitled) (Anclajes, 2025)
In her works Fotos tuyas and Las fotos, the Argentine artist Inés Ulanovsky assigns significant importance to photography as both evidence and a symbol of absences. To achieve this, she focuses on objects that seem devoid of value or were reserved solely for the intimate realm. The author brings them into light and transforms them into custodians or witnesses of other moments. In this way, she manages to create a kind of root that results in the solidification and exhibition of stories that were intended to be erased. Thanks to these books, these stories remain alive and updated. Fotos tuyas and Las fotos reveal a certain ‘filiative’ and ‘affiliative’ function. Likewise, Ulanovsky’s work with archives stands out. The mortar that holds these books together is the significance of memory and its implications for post-dictatorship Argentina.